2004
DOI: 10.1001/archpedi.158.8.737
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of School Bullying in Korean Middle School Students

Abstract: School bullying is highly prevalent in Korean middle school students. Demographic characteristics can help identify students at greater risk for participation in school bullying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
108
3
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(137 citation statements)
references
References 16 publications
19
108
3
7
Order By: Relevance
“…The results were inconsistent with those of many studies carried out in this field in various countries (1,3,5,11,15,(27)(28)(29). This prevalence rate was lower in comparison with those of some studies, especially for bully only that may contain a variety of reasons such as: good management of schools, higher peer supports, and religious beliefs that condemn bullying.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The results were inconsistent with those of many studies carried out in this field in various countries (1,3,5,11,15,(27)(28)(29). This prevalence rate was lower in comparison with those of some studies, especially for bully only that may contain a variety of reasons such as: good management of schools, higher peer supports, and religious beliefs that condemn bullying.…”
Section: Discussioncontrasting
confidence: 69%
“…School bullying, the widespread type of school violence, includes a spectrum of aggressive behaviors that involve both bullies and victims (1). Bullying is defined as a special form of aggression, which is intentional, repeated (2), and involves an imbalance of power between the victim and bullies (3).…”
Section: Introductionmentioning
confidence: 99%
“…In South Korea (Kim, Boyce, Koh, & Leventhal, 2009;Kim et al, 2004;Lee, 2001;Lee & Jun, 2011;Oh, 2014;Shin & Kim, 2014;Yang et al, 2006) boys are significantly more likely than girls to bully their peers. However, girls are more likely than boys to be perpetrators of relational aggression and social exclusion (wang-tta; Koo, Kwak, & Smith, 2008).…”
Section: Social-ecological Perspectivementioning
confidence: 99%
“…Kim et al's (2009) prospective study of 1,666 7 th and 8 th grade students found that adolescents whose father had lower educational attainment, and those whose mother had higher educational attainment, were at an increased risk for peer victimization. Family structure, particularly non-traditional structures (e.g., single parent household) is also significantly associated with bullying and peer victimization (Kim et al, 2004;Kim et al, 2009;Yang et al, 2013).…”
Section: Social-ecological Perspectivementioning
confidence: 99%
See 1 more Smart Citation